(untitled) - Northrup, Anthony (Redmond, WA, 2008)
Announcing an all-new Self-Paced Training Kit designed to help maximize your performance on 70-622, the required exam for the new Microsoft® Certified IT Professional (MCITP): Windows Vista Client Enterprise Support Technician certification. This 2-in-1 kit includes the official Microsoft study guide, plus practice tests on CD to help you assess your skills. It comes packed with the tools and features exam candidates want most--including in-depth, self-paced training based on final exam content; rigorous, objective-by-objective review; exam tips from expert, exam-certified authors; and customizable testing options. It also provides real-world scenarios, case study examples, and troubleshooting labs for skills and expertise that you can apply to the job.
Keywords: Electronic data processing personnel,Microsoft software,Phần mềm microsoft,Người xử lý dữ liệu điện tử; Certification,Examinations,Kiểm tra,Giấy chứng nhận